Application of Supply Chain Management (SCM) in Warehouse Information Systems to Increase Effectiveness and Efficiency in Warehousing - Elda Anzeli Hasibuan; M. Farhan Harahap (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Supply chain management (SCM) is a system that can coordinate the process of moving materials, information and finances within a company, one of the factors that requires costs in marketing products which is logistics management which consists of product design, material procurement, and goods storage. The coordination that occurs does not only exist within the company, the goal is for the management of raw material inventory needs to be more effective and efficient.